Promising Strategies of Colloidal Drug Delivery-Based Approaches in Psoriasis Management - Sukhbir Singh; Neelam Sharma; Tapan Behl; Bidhan Chandra Sarkar; Hasi Rani Saha; Kanika Garg; Supriya Kamari Singh; Sandeep Arora; Md. Shah Amran; Ahmed A. H. Abdellatif; Anwar L. Bilgrami; Ghulam Md Ashraf; et al. (MDPI AG, 2021)
Psoriasis is a chronic inflammatory autoimmune disorder that moderately affects social and interpersonal relationships. Conventional treatments for psoriasis have certain problems, such as poor drug penetration through the skin, hyper-pigmentation, and a burning sensation on normal and diseased skin. Colloidal drug delivery systems overcome the pitfalls of conventional approaches for psoriasis therapeutics and have improved patient safety parameters, compliance, and superior effectiveness. They also entail reduced toxicity. This comprehensive review's topics include the pathogenesis of psoriasis, causes and types of psoriasis, conventional treatment alternatives for psoriasis, the need for colloidal drug delivery systems, and recent studies in colloidal drug delivery systems for the treatment of psoriasis. This review briefly describes colloidal drug delivery approaches, such as emulsion systems-i.e., multiple emulsion, microemulsion, and nano-emulsion; vesicular systems-i.e., liposomes, ethosomes, noisomes, and transferosomes; and particulate systems-i.e., solid lipid nanoparticles, solid lipid microparticles, nano-structured lipid carriers, dendrimers, nanocrystals, polymeric nanoparticles, and gold nanoparticles. The review was compiled through an extensive search of the literature through the PubMed, Google Scholar, and ScienceDirect databases. A survey of literature revealed seven formulations based upon emulsion systems, six vesicular drug delivery systems, and fourteen particulate systems reported for antipsoriatic drugs. Based on the literature studies of colloidal approaches for psoriasis management carried out in recent years, it has been concluded that colloidal pharmaceutical formulations could be investigated broadly and have a broad scope for effective management of many skin disorders in the coming decades.